Prony's Method for Multivariate Signals. Issue 1 (21st October 2015) - Peter, Thomas; Plonka, Gerlind; Schaback, Robert
Abstract: The problem of recovering translates and corresponding amplitudes of sparse sums of Gaussians out of sampling values as well as reconstructing sparse sums of exponentials are nonlinear inverse problems that can be solved for example by Prony's method. Here, we want to demonstrate a new extension to multivariate input data. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)